Оrganizational and procedural possibilities of mediation in resolving public law disputes - Egezhanova, Д.Р.; Saktaganova, И.С.; Saktaganova, А.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
Currently, the field of administrative proceedings faces the challenge of improving the institutions of administrative justice. To this end, efforts should be directed towards the scientific exploration of the organizational and procedural potential of mediation in resolving public-law disputes. For the theoretical development of these issues, it is essential to examine international experience as well as the practice of legal regulation of the mediation institution in the administrative legislation of the Republic of Kazakhstan. The procedural aspects of mediation in civil, family, and labor disputes have found a solid place in the scientific community. However, mediation as part of administrative justice has not been the subject of serious academic research. We believe that the potential of mediation in administrative proceedings has not been fully explored from both a scientific and practical perspective. There are no well-developed legal approaches that reveal the specifics of mediation in disputes arising from public-law relations. An analysis of the available scientific literature and regulatory framework has identified existing problematic aspects that require both legal and methodological support. The conclusions and proposals formulated based on the research results have scientific value as well as theoretical and practical significance. They will help develop a solid understanding of the importance of mediation procedures within the system of administrative justice as a guaranteed mechanism for ensuring the rights and interests of parties involved in judicial proceedings.